1958
DOI: 10.1002/cite.330301109
|View full text |Cite
|
Sign up to set email alerts
|

Wärmeübergang in Blasensäulen. II. Messungen an viscosen Suspensionen

Abstract: Für verschiedene Suspensionen wurde der Wärmeübergang von einem in den Strömungskern einer Blasensäule eingehängten Heizkörper zum fluiden Medium gemessen. Hierbei wurden Gasdurchsatz, Viscosität der Flüssigkeit und Porositätsgrad der Verteilerplatten variiert. Der Wert der Wärmeübergangszahl α ist eine Funktion des Wärmewiderstandes in der sich zwischen Heizkörperoberfläche und Blasensäule ausbildenden Grenzschicht, in der die Wärme ausschließlich durch Leitung transportiert wird. Das Vorhandensein dieser Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1961
1961
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…As at high superficial liquid velocity, the superficial gas velocity at which slugging of large bubbles is initiated becomes larger with liquid velocity as reported by Kato (1957) and Inoue and Unno (1972), eq 18 is applicable for a larger superficial gas velocity. According to Kolbel et al (1958), the following relations were obtained for the laminar range of low superficial gas velocity and the turbulent range of high superficial gas velocity. The tendency of a smaller exponent for Ug at higher superficial gas velocity is same as that obtained in this work; however, exponents for Ug or µ are rather smaller than the values by other workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As at high superficial liquid velocity, the superficial gas velocity at which slugging of large bubbles is initiated becomes larger with liquid velocity as reported by Kato (1957) and Inoue and Unno (1972), eq 18 is applicable for a larger superficial gas velocity. According to Kolbel et al (1958), the following relations were obtained for the laminar range of low superficial gas velocity and the turbulent range of high superficial gas velocity. The tendency of a smaller exponent for Ug at higher superficial gas velocity is same as that obtained in this work; however, exponents for Ug or µ are rather smaller than the values by other workers.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the small ratio, 1.33, of height to diameter of the aerated tower used by them, as conditions of bubble dispersion in the aerated tower are stabilized after bubble ascending of one tower diameter length from the sparger as reported by Akita (1972). Hart (1976) reported the following dimensionless equation including the data by Kolbel et al (1958) in the correlation. The values of the exponents for various properties given by Hart are almost the same as those in eq 17 in this work.…”
Section: Resultsmentioning
confidence: 99%
“…However the value of the present exponent is greater than the value 0.269 reported by Sedahmed and Shemilt (1981) in their study of the effect of counterelectrode oxygen on the rate of mass transfer at a vertical plate cathode placed coplanar and downstream of the anode. There have been a wide range of studies on heat transfer in gas-sparged systems including those of Hikita et al (1981), Hart (19761, Fair (1967), Fair et al (1962), Ruckenstein and Smigelschi (1965), Deckwer (1980), Kast (1962Kast ( , 1963, Novosad (1954), and Kolbel et al (1958aKolbel et al ( , 1958b. This affects adversely the ability of the bubbles to enhance the rate of mass transfer at the plate cathode.…”
Section: Methodsmentioning
confidence: 99%
“…This affects adversely the ability of the bubbles to enhance the rate of mass transfer at the plate cathode. There have been a wide range of studies on heat transfer in gas-sparged systems including those of Hikita et al (1981), Hart (19761, Fair (1967), Fair et al (1962), Ruckenstein and Smigelschi (1965), Deckwer (1980), Kast (1962Kast ( , 1963, Novosad (1954), and Kolbel et al (1958aKolbel et al ( , 1958b. In general it was found that the heat transfer coefficient could be related to the superficial velocity of the gas by an equation similr to Equation (2) but with an exponent ranging from 0.15 to 0.33 depending on the value of the superficial velocity of the gas, the higher the range of superficial velocity the lower being the value of the coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…to water causes reduction of CHTC in slurry bubble columns (Kolbel et al, 1958(Kolbel et al, , 1960. Deckwer et al (1980) found that adding alumina particles with average diameter of 5 m to melting paraffin increases CHTC at superficial gas velocities lower than 0.04 m/s.…”
Section: Introductionmentioning
confidence: 98%